2018
DOI: 10.12799/jkachn.2018.29.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Analysis of Factors associated with Subjective Weight Perception among Normal Body Weight Adolescents based on the 2017 Korean Youth's Risk Behavior Survey (KYRBS)

Abstract: The present study is focused on understanding weight perception related with individual-and school-level multifactorial origins, underestimated and overestimated respectively, in normal body weight adolescents. Methods: Using the 2017 Korea Youth Risk Behavior Web-based Survey data of 45,902 students from 799 secondary schools, a multilevel multinomial logistic regression analysis was performed where adolescents (level1) were nested within schools (level 2). Results: At the school level, the average school bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…We also found that health habits and psychological problems such as smoking, alcohol consumption, high stress, and depression with improper weight control increased the probability of UEB among adolescents, consistent with other relevant studies [ 28 30 34 40 41 ]. Furthermore, our findings revealed that students with excessive BMI and lack of weight control were negatively associated with UEB.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that health habits and psychological problems such as smoking, alcohol consumption, high stress, and depression with improper weight control increased the probability of UEB among adolescents, consistent with other relevant studies [ 28 30 34 40 41 ]. Furthermore, our findings revealed that students with excessive BMI and lack of weight control were negatively associated with UEB.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies show that accurate body shape recognition is related to appropriate eating behaviors [ 13 14 15 16 17 18 19 ]. Although studies have been conducted on weight perception and related factors among Korean adolescents [ 16 28 ], only a few have determined the relationship between BSM and dietary patterns [ 14 29 30 ]. However, these studies did not examine associations with UEB using the latest Korea Youth Risk Behavior Web-based Survey (KYRBWS).…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes toward physical education knowledge had a slightly lower correlation with factor 1, suggesting less importance in comparison to other factors. The study of [ 1 ] showed that students' perceived value and role of physical activity showed a high correlation ( r =0.87) with adherence to physical activity in the long term, indicating that the perception of the value and role of physical education itself is an important factor influencing students' adherence to physical activity. This shows that there are some differences in the role played by the attitude factor of physical education knowledge in two different stages of physical activity behavior.…”
Section: Related Workmentioning
confidence: 99%
“…The obesity rate in China has doubled in the last 30 years, according to The Times, UK. The rate of obesity and overweight among adults in developing countries increased from 250 million in 1980 to 904 million in 2008, and China now has a quarter of the obese and overweight population [ 1 ]. This study analyzes the factors influencing the physical activity behavior of adolescent students to provide a theoretical reference for physical education programs aimed at improving adolescent exercise behavior and promoting adolescent health [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A national survey conducted in Canada reported that 15.8% of normal-weight female adolescents and 6.0% of normal-weight male adolescents perceived themselves as overweight [ 1 ]. These rates are even higher in South Korea, where one study found the respective percentages to be 33.7% and 20.9% [ 2 ]. Such high numbers are concerning, as adolescents who overestimate their body size are prone to extreme weight control behaviors (EWCB) [ 3 ], which thus highlights the need for evidence-based educational interventions and other relevant measures aimed at the promotion of healthy behaviors in this group.…”
Section: Introductionmentioning
confidence: 99%